Effect of potassium and mulching ameliorants on soil enzyme activities in peanut (Arachis hypogaea) crop facing salinity stress - BHADURI, DEBARATI; MEENA, H N; SAHA, AJOY; YADAV, R S; CHAKRABORTY, K; JAIN, N K; DESAI, DEEPALI (The Indian Journal of Agricultural Sciences, 2020)
Salinity in agriculture creates a menace when exceeds the threshold limit, impacting heavily both soil and plants grown on it. K-fertilizer and mulching are often proposed to control salinity. In this backdrop, our study was aimed to analyze the effect of four important soil enzymes by combined application of muriate of potash as potassium fertilizer (control, 30, 60 kg K ha-1) and mulching (with and without polythene mulch) under saline irrigation (control, 2.0, 4.0dS m-1) during the active crop growth stages (50 and 100 DAS) in peanut (Arachis hypogaea L.) crop during summer, 2014. Results revealed that polythene mulching could effectively reduce the electrical conductivity of saturation extract of soil (ECe) across the salinity levels. The differentiating effects under mulching and potassium treatments were also observed for each of the enzymes studied. Dehydrogenase, alkaline phosphatase and urease enzymes recorded more activity at 100 DAS than 50 DAS, while acid phosphatase showed a reverse trend. However, the benefits of using ameliorants like mulching and potassium fertilizer for soil biological activity under peanut crop were found to be salinity treatment specific, either at higher irrigation salinity (4.0 dS m-1) or at non-saline or lower irrigation salinity (2.0 dS m-1) plots. To reduce the impact of salinity both the ameliorants may or may not act jointly as observed in the present study. Overall, our study inevitably established the usefulness of mulching and potassium fertilizer for sustenance of soil biological health under salt-prone arid and semi-arid regions.